Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Certainly! Let’s solve the equation step by step:
[tex]\[ \log(x-1) + \log(x+1) = 2\log(x+2) \][/tex]
### Step 1: Apply the properties of logarithms
Using the property [tex]\(\log a + \log b = \log(ab)\)[/tex] on the left-hand side:
[tex]\[ \log\left((x-1)(x+1)\right) = 2\log(x+2) \][/tex]
### Step 2: Simplify the equation
Expand the left-hand side:
[tex]\[ \log(x^2 - 1) = 2\log(x+2) \][/tex]
Use the property [tex]\(a\log b = \log(b^a)\)[/tex] on the right-hand side:
[tex]\[ \log(x^2 - 1) = \log((x+2)^2) \][/tex]
### Step 3: Remove the logarithms using the property that if [tex]\(\log a = \log b\)[/tex], then [tex]\(a = b\)[/tex]:
[tex]\[ x^2 - 1 = (x+2)^2 \][/tex]
### Step 4: Expand and simplify the quadratic equation
[tex]\[ x^2 - 1 = x^2 + 4x + 4 \][/tex]
Subtract [tex]\(x^2\)[/tex] from both sides:
[tex]\[ -1 = 4x + 4 \][/tex]
### Step 5: Solve for [tex]\(x\)[/tex]
Subtract 4 from both sides:
[tex]\[ -5 = 4x \][/tex]
Divide by 4:
[tex]\[ x = -\frac{5}{4} \][/tex]
### Step 6: Verify the result
We need to ensure that the solution satisfies the original domain requirements, where the arguments of the logarithms must be positive:
- [tex]\(x - 1 > 0 \implies x > 1\)[/tex]
- [tex]\(x + 1 > 0 \implies x > -1\)[/tex]
- [tex]\(x + 2 > 0 \implies x > -2\)[/tex]
From these conditions, [tex]\(x > 1\)[/tex] is the most restrictive.
The solution [tex]\(x = -\frac{5}{4}\)[/tex] does NOT satisfy this condition.
### Conclude there are no real solutions
Therefore, there are no real values of [tex]\(x\)[/tex] that satisfy the given equation.
[tex]\[ \log(x-1) + \log(x+1) = 2\log(x+2) \][/tex]
### Step 1: Apply the properties of logarithms
Using the property [tex]\(\log a + \log b = \log(ab)\)[/tex] on the left-hand side:
[tex]\[ \log\left((x-1)(x+1)\right) = 2\log(x+2) \][/tex]
### Step 2: Simplify the equation
Expand the left-hand side:
[tex]\[ \log(x^2 - 1) = 2\log(x+2) \][/tex]
Use the property [tex]\(a\log b = \log(b^a)\)[/tex] on the right-hand side:
[tex]\[ \log(x^2 - 1) = \log((x+2)^2) \][/tex]
### Step 3: Remove the logarithms using the property that if [tex]\(\log a = \log b\)[/tex], then [tex]\(a = b\)[/tex]:
[tex]\[ x^2 - 1 = (x+2)^2 \][/tex]
### Step 4: Expand and simplify the quadratic equation
[tex]\[ x^2 - 1 = x^2 + 4x + 4 \][/tex]
Subtract [tex]\(x^2\)[/tex] from both sides:
[tex]\[ -1 = 4x + 4 \][/tex]
### Step 5: Solve for [tex]\(x\)[/tex]
Subtract 4 from both sides:
[tex]\[ -5 = 4x \][/tex]
Divide by 4:
[tex]\[ x = -\frac{5}{4} \][/tex]
### Step 6: Verify the result
We need to ensure that the solution satisfies the original domain requirements, where the arguments of the logarithms must be positive:
- [tex]\(x - 1 > 0 \implies x > 1\)[/tex]
- [tex]\(x + 1 > 0 \implies x > -1\)[/tex]
- [tex]\(x + 2 > 0 \implies x > -2\)[/tex]
From these conditions, [tex]\(x > 1\)[/tex] is the most restrictive.
The solution [tex]\(x = -\frac{5}{4}\)[/tex] does NOT satisfy this condition.
### Conclude there are no real solutions
Therefore, there are no real values of [tex]\(x\)[/tex] that satisfy the given equation.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.